1979
DOI: 10.1007/bf00563113
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoneuronal and sympathoadrenal activation during ketamine anesthesia

Abstract: The effects of ketamine anesthesia (3 mg/kg i.v.) on cardiovascular parameters and noradrenaline, adrenaline and dopamine-beta-hydroxylase (DBH) activity in plasma were studied in 12 patients. At 3, 6 and 10 min after induction of anesthesia, a pronounced increase in heart rate (+28%) and in systolic and diastolic blood pressure (+28% and 17% resp.) was observed. Concomitantly noradrenaline and adrenaline concentrations increased significantly from 187 to 415 ng/l and from 97 to 271 ng/l, respectively. DBH-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
5

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
0
20
1
5
Order By: Relevance
“…In man, this cardiovascular stimulating effect of ketamine was mainly attributable to sympathetic stimulation via a central mechanism resulting in increased circulating levels of norepinephrine and epinephrine (APPEL et al, 1979). Despite the expected cardiovascular stimulating effects of ketamine, bradycardia was observed in 23 to 30% of dogs and hypotension was observed in 70 to 77% of dogs in the present study.…”
Section: Bressan Et Alcontrasting
confidence: 53%
“…In man, this cardiovascular stimulating effect of ketamine was mainly attributable to sympathetic stimulation via a central mechanism resulting in increased circulating levels of norepinephrine and epinephrine (APPEL et al, 1979). Despite the expected cardiovascular stimulating effects of ketamine, bradycardia was observed in 23 to 30% of dogs and hypotension was observed in 70 to 77% of dogs in the present study.…”
Section: Bressan Et Alcontrasting
confidence: 53%
“…It was been shown that ketamine releases epinephrine and norepinephrine. [45][46][47][48] It is interesting to note that a substantial vasoconstriction in the intestines was observed for at least 45 minutes after ketamine injection. It has been shown that an increase in blood pressure, cardiac output, and heart rate with a concomitant increase in epinephrine and norepinephrine plasma concentrations usually do not last more than 10 to 20 minutes after ketamine injection.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamin besitzt einen zentralen sympathikomimetischen Effekt [32], der zu gesteigerten Serumspiegeln von Adrenalin und Noradrenalin führt [4,9,18] [39]. Obwohl in In-vitro-Untersuchungen nachgewiesen wurde, dass Ketamin einen dosisabhängigen direkten negativ inotropen Effekt ausübt [22,38], überwiegt in vivo offenbar die sympathische Stimulation, sodass Ketamin Anstiege von HF, MAD, SV und HZV bewirkt [4,9,19].…”
Section: Stimulation Des Sympathischen Nervensystemsunclassified